Toll-like receptor 4 inhibitor protects against retinal ganglion cell damage induced by optic nerve crush in mice - Yukimichi Nakano; Masamitsu Shimazawa; Kazuki Ojino; Hiroshi Izawa; Hiroto Takeuchi; Yuki Inoue; Kazuhiro Tsuruma; Hideaki Hara (Elsevier, 2017)
Toll-like receptor 4 (TLR4) plays key roles in innate immune responses and inflammatory reactions. TAK-242 (resatorvid) is a small-molecule cyclohexene derivative that selectively inhibits TLR4 signaling pathways and suppresses inflammatory reactions. Here we investigated the protective effects of TAK-242 against optic nerve crush (ONC) which induces axonal injury like glaucoma in mice. TAK-242 was injected intravitreally immediately after ONC. The effect of TAK-242 was evaluated by measuring the number of fluorogold-labeled retinal ganglion cells (RGCs) at 10 days after ONC. Furthermore, the expression levels of phosphorylated-nuclear factor-kappa B (p-NF-κB) and phosphorylated-p38 (p-p38) were measured by Western blotting. In addition, we examined activated astrocytes by immunostaining. TAK-242 significantly abrogated the loss of RGCs associated with ONC. Moreover, the expression levels of p-NF-κB and p-p38 were significantly reduced by TAK-242 treatment. Furthermore, TAK-242 and C34, a TLR4 inhibitor, significantly reduced astrocyte activation in the ganglion cell and inner plexiform layers, compared with vehicle treatment. These findings indicate that TAK-242 inhibits not only the TLR4 signaling pathway but also astrocyte activation downstream of this pathway, suggesting that the inhibition of TLR4 signaling is a promising candidate for the treatment of glaucoma.